Development of isothermal nucleic acid amplification technologies for rapid detection of Porcine Enterovirus-G - Sarshti Kaushik; Sushila Maan; Kanisht Batra; Swati Sindhu; Vijay Kadian; Aman Kumar (PLoS ONE, 2025)
Porcine enterovirus G (PEV-G) presents a considerable threat to the swine industry, causing a range of diseases that include diarrhea, encephalomyelitis, reproductive disorders, and respiratory infections. Conventional diagnostic approaches, such as virus isolation and RT-PCR, are frequently labor-intensive and reliant on specialized equipments. Therefore, there is an immediate need for isothermal nucleic acid amplification techniques-specifically, Recombinase Polymerase Amplification (RPA) and Polymerase Spiral Reaction (PSR) that offer rapid, sensitive, and field-deployable detection of PEV-G. In this study, we successfully developed and optimized two isothermal nucleic acid amplification assays namely RPA/RT-RPA and PSR/RT-PSR to detect PEV-G in swine populations in Haryana. Primers were specifically designed to target the polyprotein region of PEV-G for both assays. Optimal conditions regarding temperature, incubation time, primer concentration, and magnesium ion concentration were established. The RPA assay demonstrated a sensitivity of 1.417 × 10⁴ copies with a detection time of just 20 minutes. The PSR assay exhibited a lower sensitivity of 2.3 x 105 copies in comparison to RPA assay in gel based detection system and required 2.5 hours for detection. Both assays showed exceptional specificity for PEV-G, with no observable cross-reactivity with other related porcine viruses. Additionally, visual detection using Picogreen dye provided a practical solution for field use, with limits of detection of 14 copies for RPA and 2.3 copies for PSR. Validation on 100 archived field samples showed that isothermal assays have comparable sensitivity to conventional PCR. This study underscores the potential of RPA and PSR as effective and cost-efficient diagnostic tools, enabling timely and precise detection of PEV-G in both laboratory and field contexts. Such advancements are vital for improving disease management strategies and reducing economic losses within the swine industry.